Herbert Marcuse : a critical reader - Abromeit, John, 1970-; Cobb, W. Mark (William Mark), 1962- (Routledge, 2004)
The Legacy of Herbert Marcuse: A Critical Reader is a collection of brand new papers by seventeen Marcuse scholars, which provides a comprehensive reassessment of the relevance of Marcuse's critical theory at the beginning of the 21st century. Although best known for his reputation in critical theory, Herbert Marcuse's work has had impact on areas as diverse as politics, technology, aesthetics, psychoanalysis and ecology. This collection addresses the contemporary relevance of Marcuse's work in this broad variety of fields and from an international perspective. In Part One, vet.